Multistage Shelf Devices with Fluidized Bed for Heat-Mass Transfer Processes: Experimental Studies and Practical Implementation - Yukhymenko, Mykola; Artyukhov, Artem; Ostroha, Ruslan; Artyukhova, Nadiia; Krmela, Jan; Bocko, Jozef (My University, 2021)
The article deals with the theoretical description and experimental study of the hydrodynamic and heat transfer properties regarding the operation of multistage gravitational devices of the fluidized bed with inclined perforated shelves. The peculiarities of the work and the implementation field of the multistage shelf units are described. A theoretical model to define the solubilizer’s velocity above the perforation holes, in the above-shelf space of the device and in the outloading gap, as well as the residence time of the dispersed phase at the stage (perforated shelf contact) of the device is presented. The results of experimental studies regarding the influence, made by the structural parameters of the perforated shelf contacts, on the distribution pattern of single-phase and gas-dispersed flows in the workspace of the device, on the intensity of interphase heat transfer are presented. The conditions to create active hydrodynamic operating modes of multistage gravitational shelf devices, which provide higher efficiency of heat-mass transfer processes, and with lower gas consumption and hydraulic resistance compared to typical fluidized bed devices, are proved. Peculiarities regarding the implementation of heat-mass transfer processes in multistage devices are described using heat treatment and drying processes as examples.
Vícestupňová policová zařízení s fluidním ložem pro procesy přenosu teplých materiálů: experimentální studie a praktická implementace
Keywords: multistage shelf apparatus; fluidized bed; suspended layer; hydrodynamic regime; velocity profile; interphase heat transfer; cooling; drying; vícestupňové policové zařízení; fluidní lůžko; hydrodynamický režim; rychlostní profil; mezifázový přenos tepla; chlazení; sušení